Design and Development of a WooCommerce-Based E-Commerce System to Boost Sales at Koko Store - Meko Arismansah; Yetman Erwadi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The rapid growth of e-commerce in Indonesia, supported by internet penetration exceeding 77% with approximately 200 million active users, presents significant opportunities for small and medium enterprises (SMEs) to expand their market reach. However, most SMEs still face major obstacles in digital adoption, including limited capital, low digital literacy, and the absence of an integrated sales system. Koko Store, a fashion SME in Bengkulu City, exemplifies this condition, as all operational activities — including transactions, stock recording, and bookkeeping — are still conducted manually. This study aims to design and build a WooCommerce-based e-commerce system on the WordPress platform as a digital transformation solution for Koko Store. The development methodology used is the System Development Life Cycle (SDLC) with the Waterfall model, comprising five stages: requirements analysis, system design, implementation, testing, and maintenance. System testing was conducted using Black Box Testing across four system actors — visitor, customer, seller, and admin — and all functional scenarios produced results in accordance with expectations. The resulting system provides integrated features including product management, order processing, payment verification, and real-time sales reporting. The implementation of this WooCommerce-based e-commerce system is proven to improve operational efficiency, expand market reach, and increase sales volume, thereby supporting the digital transformation of Koko Store in the current digital economy era.